Numerical Simulation and Experimental Study on the Gas-liquid Two-phase Flow in the Pump During the Gas Cut-off Transition Process - F. Yang; J. Zhang; C. Shao (Journal of Applied Fluid Mechanics)
This study aims at elucidating the flow mechanism and characterizing the internal pump flow properties during the gas cut-off transition process. High-speed photography (HSP) served for visualizing the flow patterns within a transparent centrifugal pump model fabricated from plexiglass. Numerical simulation was conducted on the gas-liquid two-phase flow within the pump in the gas cut-off transition process using the Eulerian-Eulerian heterogeneous flow model coupled with the SST k-ω turbulence model. The experimental observations from HSP served as validation for the numerical simulation results. During the gas cut-off transition process, with a decreasing gas volume fraction (GVF), the pressure in the volute gradually increases until it ultimately exhibits periodic variation. The time-averaged pressure exhibits a steady increase with the flow. The GVF slowly diminishes along volute’s radial direction. As a consequence of impeller rotation, the outlet pressure rises with the decreasing integral rate of the gas phase inside the impeller. Concurrently, the integral rate at the outlet has not yet changed, so the change in outlet GVF consistently lags behind the change in outlet pressure. The centrifugal pump completes the gas cut-off transition process when fluctuations in the outlet GVF cease. This investigation revealed the temporal evolution of GVF and pressure during the centrifugal pump's gas cut-off transition process, and established a quantitative criterion for determining the completion of this process. The research results are beneficial for more deeply comprehending the pump's performance, and well contribute to the reliable operation and structural optimization pertaining to centrifugal pumps.